2019
DOI: 10.1007/s11420-019-09677-z
|View full text |Cite
|
Sign up to set email alerts
|

Static Versus Expandable Devices Provide Similar Clinical Outcomes Following Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Background: Few studies have analyzed differences in radiographic parameters and patient-reported outcomes (PROs) between expandable and static interbody devices in patients undergoing minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Questions/Purposes: To evaluate differences in radiographic parameters and PROs following MIS TLIF between static and expandable interbody devices. Methods: Patients undergoing primary, single-level MIS TLIF between 2014 and 2017 were retrospectively identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…These results were also commensurate with previous studies of expandable devices, which reported 12-month fusion rates ranging from 92% to 96%. 9,[21][22][23] Furthermore, Khechen et al 8 reported the proportions of patients reaching MCID for ODI, VAS leg, and VAS back at 6 months follow-up after TLIF with an expandable device to be 60%, 70%, and 67%, respectively, which were similar to the 58%, 71%, and 76% observed in the current study at a mean follow-up of 4.5 months. Similarly, Alimi et al 24 reported that 64%, 52%, and 52% of patients treated with an expandable device reached the MCID for ODI, VAS leg, and VAS back by an average of 19.3 months follow-up, but the MCID used for VAS was 3 points in that study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These results were also commensurate with previous studies of expandable devices, which reported 12-month fusion rates ranging from 92% to 96%. 9,[21][22][23] Furthermore, Khechen et al 8 reported the proportions of patients reaching MCID for ODI, VAS leg, and VAS back at 6 months follow-up after TLIF with an expandable device to be 60%, 70%, and 67%, respectively, which were similar to the 58%, 71%, and 76% observed in the current study at a mean follow-up of 4.5 months. Similarly, Alimi et al 24 reported that 64%, 52%, and 52% of patients treated with an expandable device reached the MCID for ODI, VAS leg, and VAS back by an average of 19.3 months follow-up, but the MCID used for VAS was 3 points in that study.…”
Section: Discussionsupporting
confidence: 83%
“…es. 8,9,[21][22][23][24]30 Therefore, further prospective and randomized clinical trials are warranted to substantiate the positive, preliminary findings reported in the present study.…”
Section: Disclosures and Coimentioning
confidence: 81%
See 2 more Smart Citations
“…Широко описаны варианты техник минимально инвазивного TLIF [7][8][9][10] и обозначены их преимущества, такие как меньшая раневая площадь, малый объем кровопотери, быстрое заживление послеоперационной раны, низкая частота осложнений, меньшая выраженность болевого синдрома в послеоперационном периоде и, как следствие, низкая потребность в анальгетиках, ранние активизация пациентов и начало восстановительного периода, сокращение времени пребывания в стационаре и скорое возвращение к активной деятельности [11][12][13].…”
unclassified